Application of SVC on IEEE 6 Bus System for Optimization of Voltage Stability - Sita Singh; Jitendra Hanumant; Ashutosh Kashiv (IAES Indonesian Section, 2015)
The problem of voltage or current unbalance is gaining more attention recently with the increasing awareness on power quality. Excessive unbalance among the phase voltages or currents of a three phase power system has always been a concern to expert power engineers. The study of shunt connected FACTS devices is an associated field with the problem of reactive power compensation related problems in today’s world. In this study an IEEE-6 bus system has been studied & utilized in order to study the shunt operation of FACTS controller to optimize the voltage stability